Modifikasi media bola busa terhadap pembelajaran servis bawah bola voli pada siswa kelas VIII - Umam, Fachtur Nahdhil; Abduloh, Abduloh; Achmad, Irfan Zinat (Universitas Hamzanwadi, 2024)
The problem of this research is the movement of the lower serve in volleyball learning. This study aims to examine, analyze, and identify a significant effect of using foam ball media modification on basic lower serve movement skills. This study uses a quantitative approach with a pre-experimental technique of the one-group pretest posttest design. The sampling technique used purposive sampling which amounted to 124 students. The population is the entire class with the research sample is class VIII. The results of research and data analysis show that the hypothesis proposed in this study is accepted, there is an average value of the research sample in the pretest and posttest scores increased by 86.78 from the initial service movement stage, core service movement and final service movement. Based on the results of the mean rank value of the pretest 63.37 and posttest 185.63, meaning that the posttest results are greater than the mann-whitney test pretest with the “test statistics” output, it is known that the Asymp .Sig (2-tailed) value is 0.000 < 0.05, it can be concluded that the hypothesis is accepted and there is a significant difference in influence on the basic technical ability of volleyball lower serve.